ANALISIS PERAN ADMINISTRASI PENDIDIKAN ISLAM DALAM MENINGKATKAN EFEKTIVITAS PROSES PEMBELAJARAN: STUDI LITERATUR - Muhamamad Ikhsan; Ana Setiyani Mutia; Windi; Nur Emilia; M. Hastiavin Habibi; Adinata (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Islamic educational administration plays an important role in supporting the effectiveness of the learning process in educational institutions. This study aims to analyze the role of Islamic educational administration in improving learning effectiveness through a literature study. The research method used is library research by reviewing various scientific sources such as books, journals, articles, and other relevant academic references. The data analysis technique employed is content analysis with a thematic approach. The results indicate that Islamic educational administration contributes to creating organized, disciplined, conducive, and effective learning processes. Proper administration also helps improve teacher quality, facilitates learning management, and supports the development of students’ Islamic character. In addition, learning effectiveness is influenced by supporting factors such as human resource quality, leadership, educational facilities, and the use of technology. Therefore, Islamic educational administration becomes an essential component in improving educational quality and the success of learning processes in Islamic educational institutions